An Exploration of the Impact of the COVID-19 Pandemic on Allied Health Students; Practice Placement Experiences: The impact of the COVID-19 pandemic on students’ placement experiences - Tan, Garret (International Journal of Practice-based Learning in Health and Social Care, 2024)
The COVID-19 pandemic was an unexpected event, significantly impacting global populations. Due to its sudden occurrence, it has affected pillars of world stability, namely, healthcare. Not only has it stretched healthcare systems beyond their capacity, but it has disrupted its daily protocols and activities. As a result, adaptations to tackle this pandemic have been implemented, putting healthcare education, specifically, practice placements as a lesser priority; affecting students in a myriad of ways. Nevertheless, guidance has now been provided to allow clinical placements to continue. However, these changes have potentially limited students in their learning, posing the question of clinical sufficiency and competency. Hence, this qualitative study aims to understand the specific changes to Trusts and how students adapted to fulfil their module criteria and learning outcomes. A convenience sample of physiotherapy and occupational therapy students was recruited; from it, 18 interviews were then conducted. Transcriptions, coding and thematic analysis identified four main themes of learning opportunities, organisational changes, adaptations and mental wellbeing, thus providing clarity regarding how students successfully completed and met their placement learning outcomes despite organisational changes. However, as a result of these changes, mental and physical wellbeing has also been affected. The findings did shed light on which changes were helpful and which needed modification. Hence, future research was suggested to gain a more holistic understanding of the needs of students and other effective coping mechanisms, providing a more balanced placement experience during these uncertain times.